Upaya Meningkatkan Pendapatan Asli Daerah (PAD) Melalui Pengembangan Potensi Pariwisata Kabupaten Manggarai Barat Periode 2019-2022: Studi Kasus Di Wisata Alam Gua Rangko Labuan Bajo - Ignasia Ayunanda Duhu; Petrus E. De Rozari; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to understand the government's efforts in increasing local revenue (PAD) through the development of tourism potential in West Manggarai Regency during the 2019-2022 period, specifically focusing on the natural tourism of Rangko Cave. The process of developing tourism potential, particularly the natural tourism of Rangko Cave, requires government efforts to overcome existing challenges by using strategies to increase the PAD of West Manggarai Regency. This research employs a descriptive qualitative approach, conducting structured interviews with informants such as the Head of the Regional Revenue Agency, the Head of the Tourism Office of West Manggarai Regency, the Head of Tanjung Boleng Village, employees of the Regional Revenue Office, employees of the Tourism Office of West Manggarai Regency, and the residents of Tanjung Boleng Village. The results show that the West Manggarai government and the residents of Tanjung Boleng Village have made efforts and strategies to increase local revenue through the development of tourism potential, particularly the natural tourism of Rangko Cave, as best as possible despite several obstacles, such as a lack of supporting facilities for good and structured services, which reduce the value of the tourism site.